Textile-based pressure sensor arrays: A novel scalable manufacturing technique - TUNÇAY ATALAY, ASLI (My University, 2022)
© 2022 The AuthorsSoft pressure sensors have sparked a lot of interest over the last decade because of their applications in human motion recognition, object detection, and human–computer interaction. However, their mass production and availability to end users are limited due to the complex and time-consuming steps. The scalability of working range for various applications is also a critical challenge. Therefore, a laborless, rapid, and scalable manufacturing technique for capacitive-based soft pressure sensors with high sensitivity and high working range is proposed in this work. The novel manufacturing method enables manipulation of sensor properties by varying production parameters based on specific application needs. The proposed sensor\"s electrode is made of conductive knit fabric, and the dielectric layers are made of thermoplastic polyurethane (TPU) sheets. As a result of the novel approach, it is possible to generate scalable air gaps between electrodes and dielectric layers to capture low pressures of less than 1 kPa. The usage of multi-layer TPU sheets also increases the working range of sensors up to 1000 kPa. Here, the proposed technology is successfully applied to create several sensor mats for different purposes such as improved gesture and shape recognition, and interactive gaming mats for children.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; Fizik; Atom ve Molekül Fiziği; Yoğun Madde 1:Yapısal, Mekanik ve Termal Özellikler; Kimya; Fizikokimya; Temel Bilimler; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Signal Processing; Physics; Atomic and Molecular Physics; Condensed Matter 1: Structural, Mechanical and Thermal Properties; Chemistry; Physical Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; KİMYA, FİZİKSEL; FİZİK, YOĞUN MADDE; FİZİK, ATOMİK, MOLEKÜLER VE KİMYASAL; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; CHEMISTRY; PHYSICS; ENGINEERING, ELECTRICAL & ELECTRONIC; CHEMISTRY, PHYSICAL; PHYSICS, CONDENSED MATTER; PHYSICS, ATOMIC, MOLECULAR & CHEMICAL; Elektronik, Optik ve Manyetik Malzemeler; Fizik Bilimleri; Atom ve Moleküler Fizik ve Optik; Yoğun Madde Fiziği; Yüzeyler, Kaplamalar ve Filmler; Elektrik ve Elektronik Mühendisliği; Electronic, Optical and Magnetic Materials; Physical Sciences; Atomic and Molecular Physics, and Optics; Condensed Matter Physics; Surfaces, Coatings and Films; Electrical and Electronic Engineering; Capacitive pressure sensors; Smart textiles; E-textiles; Textile-based sensors; Gesture recognition; Interactive devices; Capacitive pressure sensors; Smart textiles; E-textiles; Textile-based sensors; Interactive devices